PENGARUH PROMOSI DAN HARGA TERHADAP MINAT BELI KONSUMEN PADA PT. PRIMADELTA STARLESTARI RANGKASBITUNG - Iwan Ridwan; Muhi Mukti; Intan Melasari (The Asia Pacific Journal Of Management Studies, 2021)
This study is to determine the factors that influence Consumer Purchase Interest through Promotion and Prices at the company PT. Primadelta Starlestari Rangkasbitung. The objectives of this study are (1) to find out the Effect of Promotion on Consumer Purchase Interest (2) to determine the Effect of Price on Consumer Purchase Interest (3) to find out Promotions and Prices on Consumer Purchase Interest at PT. Primadelta Starlestari Rangkasbitung.The method used in this research is quantitative descriptive research method. The sampling technique used was Random Sampling, which is a sampling technique that provides equal opportunities for each element (members), the sample of this study consisted of 100 respondents.Testing of this study was carried out using the classic assumption test, then analyzed by correlation test and multiple linear regression test using the SPSS VERSY 20 Program.The results showed that there was a partial correlation between Promotion and Consumer Purchase Interest, the results of the t test in the Promotion obtained t-count> t-table (3.231> 1.985). The results showed there was a partial between Price to Consumer Purchase Interest, the results of t test on Prices obtained t-count> t-table (6.169> 1.985).F test results show the f-count of 26.308 with a significance of 0,000 and f-table = 30.9. So it can be concluded that simultaneously the Promotion (X1) and Price (X2) variables have a significant effect on Consumer Purchase Interest (Y).